Regional model code of practice for psycho-social practitioners in HIV & AIDS care - Francis, Claudette (PANCAP Coordinating Unit GeorgetownGY, 2008)
Provides a set of common principles and standards to guide the provision of psycho-social support for HIV and AIDS.